A two-gun Cyclone : a true story - Denton, B. E. (Tufts University. Tisch Library., 2023)
The beginnin' -- Hoss race and my brush with Heck Thomas, U. S. Marsha -- Ropin' an antelope and earnin' a name -- Ridin' herd -- The black stallion -- Campin' in the Rockies -- Buffalo huntin' -- In a stampede on the Montana trail -- Helena, Montana, jamboree -- Before an Osage Indian chief -- The killin' of Teague -- Rough ridin' through Arkinsaw -- A long horn caught by the short horns -- Swappin' cow tales with the log rollers -- A plainsman in the blue-grass -- From Kentucky back to God's country -- Gettin' two wild stallions at once -- The death of Topsy in the Oklahoma run -- The endin' -- Some songs I remember.